Evaluation of the Quality of Drinking Mineral Waters Commercialized in Niterói Municipality- RJ - Portugal, Daniele de Souza; Silva, Camila Rodrigues e; Machado, Daniela Vasconcelos; Lima, Luana Alves de; Silva-Filho, Emmanoel Vieira da (Anuário do Instituto de Geociências, 2019)
The consumption of mineral water has grown worldwide and is associated with growing concern about water quality, in part due to the pollution of surface water bodies and the search for a healthier lifestyle. According to the National Department of Mineral Production (DNPM), in 2014, Brazil remained the 5th largest bottled water market in the world and the 8th largest producer in the world, consuming 19.5 billion liters. Faced with the wide demand for good quality water, it is necessary constant monitoring bottled mineral water. This work aims to determine if the physicochemical characteristics of bottled mineral waters consumed in the municipality of Niterói are in accordance with what is presented on the water bottle label and with Brazilian legislation. To attend this objective, physicochemical, ionic, and microbiological analyses were performed in four distinct brands over four months. The analyzed waters can be classified as sodium and calcium bicarbonate. The obtained results show that the mineral waters studied are according to the limits established by the Brazilian legislation. However, the concentrations of the larger dissolved ions were higher than the one described on the label, indicating a possible geochemical evolution of the water collected from the sources.